Filmography of social issues a reference guide - Mitchell, Charles P. 1949- (Gale virtual reference library, 2004)
Examines twenty specific social themes and shows how they are examined in a hundred motion pictures. Intended to serve as a guide for individuals interested in motion pictures and how they reflect and comment on the major issues of our time.